2021
DOI: 10.1007/s00417-021-05431-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcome and satisfaction survey in patients with neurotrophic keratopathy after treatment with cenegermin eye drops or amniotic membrane transplantation

Abstract: Purpose Neurotrophic keratopathy (NK) is a degenerative corneal disease caused by damage of trigeminal innervation. The purpose of this study is to evaluate the clinical outcomes and patient-reported satisfaction of treatment with amniotic membrane transplantation (AMT) or cenegermin eye drops in patients with NK. Methods Clinical charts of patients with NK treated with AMT (group A) or cenegermin eye drops (group B), with at least 12 months of follow-up, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Both treatments proved to heal NK within 8 weeks in our patients, but with different mechanisms: AS seems to restore the ocular surface providing some neural healers when administered (Matsumoto et al, 2004) and, in four cases, it required to be continued over time to maintain healing; cenegermin, by addressing the underlying cause, induces recovery of corneal nerves, and then it seems to ensure a stable framework even when discontinued with less risk of recurrence (Sacchetti et al, 2021). As recently reported by Pflugfelder et al (2020), variables such as disease stage, time since diagnosis, and underlying etiologies did not significantly affect the healing status.…”
Section: Discussionmentioning
confidence: 79%
“…Both treatments proved to heal NK within 8 weeks in our patients, but with different mechanisms: AS seems to restore the ocular surface providing some neural healers when administered (Matsumoto et al, 2004) and, in four cases, it required to be continued over time to maintain healing; cenegermin, by addressing the underlying cause, induces recovery of corneal nerves, and then it seems to ensure a stable framework even when discontinued with less risk of recurrence (Sacchetti et al, 2021). As recently reported by Pflugfelder et al (2020), variables such as disease stage, time since diagnosis, and underlying etiologies did not significantly affect the healing status.…”
Section: Discussionmentioning
confidence: 79%
“…Neurotrophic keratopathy is a progressive disease that leads to recurrent breakdowns of the ocular surface and despite various medical and surgical therapies, NK remains yet challenging to treat.In fact conventional treatments including use of topical lubricants, serum drops, bandage contact lenses, amniotic membranes transplantation and tarsorrhaphy showed variable healing rates in NK and few data are available on their long-term efficacy..Specifically small studies reported a recurrence rate 1-months after AMT treatment ranging from 18 to 46% [16,17].In addition, in many cases these conventional treatments often do not address the underlying cause of NK but rather only promote corneal healing [1,4]. In our study, we observed maintenance of corneal healing throughout the 48 months of follow-up in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional therapy for acute neurotrophic pathology would be bland or antibiotic ointment, bandage contact lenses, amniotic membrane, and cenegermin-bkbj 0.002% ophthalmic solution (Oxervate; Dompe, Milan, Italy). 12,[16][17][18][19] Long-term therapy for recurrent neurotrophic disease could involve options such as a partial lateral tarsorrhaphy, a conjunctival flap, cenegermin, or scleral contact lenses. 12,17,18 Although both amniotic membrane and cenegermin-bkbj 0.002% ophthalmic solution are seemingly effective in managing acute neurotrophic pathology, with cenegermin having the added benefit of being effective at reducing recurrence of neurotrophic disease, they each have some limiting features.…”
Section: Discussionmentioning
confidence: 99%
“…12,17,18 Although both amniotic membrane and cenegermin-bkbj 0.002% ophthalmic solution are seemingly effective in managing acute neurotrophic pathology, with cenegermin having the added benefit of being effective at reducing recurrence of neurotrophic disease, they each have some limiting features. 16,19 Even when applied to a neurotrophic cornea, ring bound amniotic membranes (Prokera; Biotissue, Miami, FL) can sometimes be uncomfortable enough to limit their use. Furthermore, the cost of amniotic membrane varies based on type and source and can range from several hundred dollars to more than a thousand dollars.…”
Section: Discussionmentioning
confidence: 99%